Comprehensive Characterization of Raw and Oxalic Acid Treated Ripen Cellulosic Biofiber from Areca Catechu Inflorescence as Substitute for Harmful Synthetic Products - Arabilachi, Srinivas; Govindappa, Sreenivasa Challakere; Nagaraj, Bharath Kurki; Bright, Brailson Mansingh; Binoj, Joseph Selvi (Journal of Research Updates in Polymer Science, 2025)
The inherent characteristics of natural fibers include a low density and a high strength-to-weight ratio, making them promising candidates for lightweight applications. The mechanical features of these strands are prejudiced by their chemical compositions and the cross-sectional area being the most variable factor affecting strength. In this research, strands were obtained by processing the ripen inflorescence of Areca tree and subjected to treatment with an oxalic acid (C2H2O4) solution to enhance their properties. The extracted fibers underwent examination for chemical, physical, mechanical, and morphological properties. The study findings indicate that fibers treated with a 4 wt.% C2H2O4 solution for 60 min exhibit superior properties. The strands segregated from the ripen inflorescence of areca tree treated with 4 wt.% C2H2O4 solution for 60 min exhibited a rise in cellulose proportion by 26.7%, tensile strength by 13.5%, crystallinity index by 16.6%, thermal endurance by 6.3% and appreciable surface roughness compared to the untreated fibers as viewed through Scanning Electron Microscope (SEM). The Fourier Transform Infrared (FTIR) analysis endorsed the observations of chemical analysis. The characterization of areca inflorescence fibers in this study highlights significant advantages for the advancement of composite materials.